Oracles & Cycphers - Blonk, Jaap 1953- (Redfoxpress, 2024)
"C'est mon dada: collection for visual poetry, experimental texts and works influenced by Dada and Fluxus."--Colophon
Keywords: concrete poetry; visual poetry; Concrete poetry; Visual poetry; Poésie concrète; Poésie visuelle